Penerapan E-Procurement Dalam Mendukung Layanan Pengadaan Barang Dan Jasa Di Dinas Pekerjaan Umum Dan Penataan Ruang Kota Tangerang - Nurhasan, Widia; Hilman, Hilman; Firdiyani, Fitria (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Electronic procurement of goods and services, or e-procurement, enables innovation in government and leverages technology platforms to obtain better information, better cost performance, greater efficiency, and maximize the effectiveness of e-procurement. It is an information system that transforms. The purpose of this study is to determine the "implementation of e-procurement in the support of goods and services in the public works and spatial planning sector of Tangerang Municipality". A qualitative research method was used in this study. The data sources used are primary data from interviews and observations and secondary data from documents and relevant regulations. The variables used are a) efficiency, b) effectiveness, c) competitiveness, d) transparency, and e) accountability. The survey shows that the implementation of e-procurement to support the procurement services for goods and services at the Tangerang PUPR office is on track and provides greater transparency to the public. Human resources as well as facilities and infrastructure are one of the factors that influence the process of conducting e-procurement for the public to be successful, but if the effort still causes disruption to the system. there is. By increasing the server capacity, you can continue to use it properly. At the civil engineering office.